A Novel Biomimetic Hydrogen Peroxide Biosensor Based on Pt Flowers‐decorated Fe3O4/Graphene Nanocomposite. Issue 6 (4th April 2017) - Zhao, Xueling; Li, Zhanhong; Chen, Cheng; Wu, Yihua; Zhu, Zhigang; Zhao, Hongli; Lan, Minbo
Abstract: A sensitive and selective amperometric H2 O2 biosensor was obtained by utilizing the electrodeposition of Pt flowers on iron oxide‐reduced graphene oxide (Fe3 O4 /rGO) nanocomposite modified glassy carbon electrode (GCE). The morphology of Fe3 O4 /rGO and Pt/Fe3 O4 /rGO was characterized by transmission electron microscopy (TEM) and scanning electron microscopy (SEM), respectively. The step‐wise modification and the electrochemical characteristics of the resulting biosensor were characterized by cyclic voltammetry (CV) and chronoamperometry methods. Thanks to the fast electron transfer at the Pt/Fe3 O4 /rGO electrode interface, the developed biosensor exhibits a fast and linear amperometric response upon H2 O2 . The linear range of Pt/Fe3 O4 /rGO is 0.1∼2.4 mM (R 2 =0.998), with a sensitivity of 6.875 μA/mM and a detection limit of 1.58 μM (S/N=3). In addition, the prepared biosensor also provides good anti‐interferent ability and long‐term stability due to the favorable biocompatibility of the electrode interface. The proposed sensor will become a reliable and effective tool for monitoring and sensing the H2 O2 in complicate environment. Abstract :